2022
DOI: 10.1177/23779608221075165
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve Compliance with Clinical Nursing Documentation Guidelines in the Acute Hospital Setting: A Systematic Review and Analysis

Abstract: Introduction This systematic review attempts to answer the following question – which strategies to improve clinical nursing documentation have been most effective in the acute hospital setting? Methods A keyword search for relevant studies was conducted in CINAHL and Medline in May 2019 and October 2020. Studies were appraised using the Joanna Briggs Institute (JBI) critical appraisal for quasi-experimental studies. The studies were graded for level of evidence according to GRADE principles. The data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…In line with the previous author, organized documentation describes all the patient needs, assessment, and corresponding interventions (Muhlisin, 2011). Documentation in the proper format allows for easier updating by nurses (Bunting & de Klerk, 2022;De Groot et al, 2022). Moreover, collaborative actions with other health teams must be included as implementation of patient-centered care, and in order to improve patients' satisfaction (Purwandari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the previous author, organized documentation describes all the patient needs, assessment, and corresponding interventions (Muhlisin, 2011). Documentation in the proper format allows for easier updating by nurses (Bunting & de Klerk, 2022;De Groot et al, 2022). Moreover, collaborative actions with other health teams must be included as implementation of patient-centered care, and in order to improve patients' satisfaction (Purwandari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Still, workload issues, time management, and reliance on tachycardia alone to detect pain could have contributed to the 80% upper compliance limit. Similar to previous studies, noncompliant nurses accepted the individual unmasked feedback [28][29][30][31] as we provided it in a nonthreatening confidential manner, and we did not report it to managers.…”
Section: Discussionmentioning
confidence: 87%
“…A common feature of most literature that concerned education on nursing documentation was concern about the lack of high-quality studies that addresses this need. [5][6][7] The majority of papers reviewed were either not specific to nurses or focused on the academic training rather than professional practice and development where the intervention was aimed. CRRT is a specialized treatment modality and other than basic principles it is unlikely to be covered in undergraduate nursing education, [8] making this particularly challenging for the project.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Lastly, most studies showed that a multi-modal and longitudinal approach were superior at creating effective learning. [6,7,13] Educational strategies that applied to this project included performing a pre and post-intervention assessment, [5,14] including communicationbased affective content to increase caring, [15] and including personal feedback. [6]…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation